The development of optimized production planning and control systems for the VWSA Engine Manufacturing Plant - Van Niekerk, Frank S.A.(Frank Stephen Albertus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MIng) -- Stellenbosch University, 1998.